Diagnosis and Management of Oral Extraintestinal Manifestations of Pediatric Inflammatory Bowel Disease. Issue 1 (16th September 2021) - Shazib, Muhammad Ali; Byrd, Kevin M.; Gulati, Ajay S.
Abstract : ABSTRACT: Inflammatory bowel diseases (IBD) represent a group of chronic inflammatory disorders of the gastrointestinal tract that lead to impaired quality of life and substantial health care costs. Up to 50% of pediatric IBD cases present with manifestations in the oral cavity. These may develop in nearly every oral tissue, including the soft tissues, tongue, lips, teeth, and lymph nodes. The goal of this review is to offer a systematic approach to diagnose and manage commonly encountered oral manifestations of pediatric IBD. This knowledge is critical for enhancing the comprehensive care and quality of life of children with these debilitating diseases.